A High Performance Terahertz Photoconductive Antenna Array Detector With High Synthesis Efficiency - Shi, Wei; Wang, Zhiquan; Hou, Lei; Wang, Haiqing; Wu, Meilin; Li, Chaofan (Frontiers in Physics, 2021)
A 2 × 2 terahertz photoconductive antenna (PCA) array detector with high efficiency synthesis characteristic that improves the signal-to-noise ratio (SNR) of the detected signals has been reported in this paper. By processing the substrate material through a special micromachining process, the current signal generated by the adjacent antenna elements as opposed to that generated by the antenna gap is eliminated. Experiments show that the amplitude of the current signal output by the PCA array detector is consistent with the amplitude of the synchronous superposition of the current signals output by antenna elements, and the synthesis efficiency of the device achieves 93.7%. At the same time, the antenna array detector has low current noise, and its highest SNR is 62 dB under the excitation of different light energy, which is related to the number of antenna array elements.